Peningkatan Hasil Belajar Siswa Kelas IV SDN Gayam 1 Kota Kediri melalui Model Teams Games Tournament berbantuan Kartu Domino pada Materi Pengukuran Luas dan Volume - Faridhotuz Zulfa; Kharisma Eka Putri; Novi Rohmawati (Universitas Nusantara PGRI Kediri, 2025)
The purpose of this study was focused on efforts to improve the Mathematics learning outcomes of fourth-grade students. Thus, the study was directed at finding ways to optimize student learning outcomes. This step was implemented through the implementation of the Teams Games Tournament (TGT) model combined with the use of domino cards as a medium. The research subjects consisted of 28 students and was carried out in two cycles using quantitative methods. The findings of this study showed a positive development in student learning outcomes. In other words, student learning outcomes improved after the research was conducted. Learning completeness, which was initially only 7.1% in the pre-action stage, increased to 89.2% in cycle I. Furthermore, in cycle II, the completeness reached 97%. The average student score showed an increase, namely from 67.8 initially to 90.3. In other words, there was a significant increase in student learning outcomes. In conclusion, the implementation of the TGT model assisted by domino cards was able to have a positive impact on improving student learning outcomes.